2023
DOI: 10.1111/dme.15120
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐month psychosocial outcomes of continuous glucose monitoring with behavioural support in parents of young children with type 1 diabetes

Abstract: Aim: Managing type 1 diabetes in young children can cause significant stress for parents. Continuous glucose monitoring (CGM) may reduce parental burden. The Strategies to Enhance CGM Use in Early Childhood (SENCE) trial randomized parents of children (ages 2 to <8 years) with type 1 diabetes to CGM with family behavioural intervention (CGM + FBI), CGM alone (Standard-CGM) or blood glucose monitoring for 26 weeks before receiving CGM + FBI (BGM-Crossover). This report assesses changes in psychosocial outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The opinions of healthcare workers established using Delphi methodology indicated a need for specialized and expert staff (specialized nurses, educators) to train PWD on technologies applied to diabetes ( 91 ). Behavioral interventions for family members have shown persistent psychosocial benefits.…”
Section: Fear Of Hypoglycemia and Psychological Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…The opinions of healthcare workers established using Delphi methodology indicated a need for specialized and expert staff (specialized nurses, educators) to train PWD on technologies applied to diabetes ( 91 ). Behavioral interventions for family members have shown persistent psychosocial benefits.…”
Section: Fear Of Hypoglycemia and Psychological Impactmentioning
confidence: 99%
“…Behavioral interventions for family members have shown persistent psychosocial benefits. CGM-focused education with behavioral support probably helps parents of young children with T1D reduce short- and long-term burden and worries ( 91 ). Furthermore, a telehealth approach may be helpful in the treatment of FoH ( 92 ).…”
Section: Fear Of Hypoglycemia and Psychological Impactmentioning
confidence: 99%
“…The study faced recruitment challenges and high attrition, and had only minimal impact on parenting behavior with no significant changes in glycemia, child behavior or QoL. Another RCT ( n = 131 families; child age 5.7 ± 1.8 years) tested the efficacy of continuous glucose monitoring (CGM) with a family behavioral intervention (CGM+FBI) compared to CGM alone; a crossover group received usual care followed by CGM+FBI [10 ▪▪ ]. The FBI consisted of five sessions addressing common challenges encountered by parents of young children using T1D technology.…”
Section: Psychosocial and Behavioral Interventions For Children With ...mentioning
confidence: 99%
“…With respect to glycemia, nine studies reported favorable changes [12 ▪ ,13 ▪▪ ,14 ▪ ,15 ▪ ,22 ▪ ,23,26 ▪ ,28 ▪▪ ,30 ▪▪ ], seven found no change [9,10 ▪▪ ,16 ▪ ,18,19 ▪ ,21,31 ▪ ], and one reported an increase in HbA1c among intervention recipients [20 ▪ ]; five studies did not evaluate or report glucose metrics [8 ▪ ,24,25 ▪▪ ,27 ▪ ,29 ▪ ]. Psychosocial care is important independent of its relationship to glucose, and should be provided irrespective of the likelihood of improving glycemia.…”
Section: Overall Trends In Interventionsmentioning
confidence: 99%